2019
DOI: 10.3390/cells8050502
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of Hippo Signaling Transducers Yap and Taz in Chromatin Remodeling

Abstract: Hippo signaling controls cellular processes that ultimately impact organogenesis and homeostasis. Consequently, disease states including cancer can emerge when signaling is deregulated. The major pathway transducers Yap and Taz require cofactors to impart transcriptional control over target genes. Research into Yap/Taz-mediated epigenetic modifications has revealed their association with chromatin-remodeling complex proteins as a means of altering chromatin structure, therefore affecting accessibility and acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 79 publications
1
40
0
Order By: Relevance
“…At this time, the specific factors that participate in the separation of both programs are still a matter of study [ 55 , 56 ]. Recent studies have suggested that the YAP and TAZ effectors for the WNT and Hippo pathways mediate epigenetic modifications in association with the chromatin-remodeling proteins, therefore affecting accessibility and activity of target genes [ 57 ]. Considering that the WNT and Hippo pathways participate in the maintenance of the NSPCs pool [ 58 ], in this study, we investigated the specific role of TAZ in neurogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…At this time, the specific factors that participate in the separation of both programs are still a matter of study [ 55 , 56 ]. Recent studies have suggested that the YAP and TAZ effectors for the WNT and Hippo pathways mediate epigenetic modifications in association with the chromatin-remodeling proteins, therefore affecting accessibility and activity of target genes [ 57 ]. Considering that the WNT and Hippo pathways participate in the maintenance of the NSPCs pool [ 58 ], in this study, we investigated the specific role of TAZ in neurogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, a newly emerging research frontier on how YAP/TAZ modulate stem cell function, are their novel roles in effecting epigenetic modifications to chromatin structure ( Hillmer and Link, 2019 ) and post-transcriptional miRNA processing ( Chaulk et al, 2014 ; Mori et al, 2014 ). Epigenetic modifications mediated by YAP/TAZ are effected by their association with chromatin-remodeling complexes proteins such as Nucleosome Remodeling and Deacetylase (NuRD), Switch/sucrose non-fermentable (SWI/SNF), Ncoa6, Mediator, and GAGA, which in turn influence the accessibility and activity of various target genes via alterations to chromatin structure ( Hillmer and Link, 2019 ). Post-transcriptional processing of miRNA is known to be regulated by YAP/TAZ via their binding interactions with p72 (DDX17) that regulates Microprocessor activity ( Mori et al, 2014 ), as well as by modulation of Dicer activity through the LIN28/Let-7 axis ( Chaulk et al, 2014 ).…”
Section: Conclusion and Future Outlookmentioning
confidence: 99%
“…YAP1 itself has no transcriptional activity, it is a transcriptional co-activator when combined with its TAZ and TEADs [19]. All of these three components are indispensable for downstream transcripts boost, therefore, the nuclear translocation of YAP1 is the key regulatory manner, and this process is blocked by Hippo pathway when it is in the"on"state [20,21]. The"on"state of the Hippo pathway is considered as tumor suppressive functions, since amounts of researches revealed its"on" state is capable of inhibiting cell proliferation, promoting apoptosis and regulating stem/progenitor cell expansion [20,21].…”
Section: Discussionmentioning
confidence: 99%